Biotechnological and industrial applications of Streptomyces metabolites. (5th October 2021) - Khushboo; Kumar, Punit; Dubey, Kashyap K.; Usmani, Zeba; Sharma, Minaxi; Gupta, Vijai Kumar
Abstract: Streptomyces sp. produces clinically important bioactive compounds with anticancer, antiviral, and antibacterial properties. These compounds have important roles in various fields like agriculture, and medicine, with bio‐economic benefits. Progress in genome mining has resulted in the characterization of various secondary metabolites such as lipstatin, macrolide lactones, clavulanic acid, and cholesterol oxidase. Integration of DNA sequencing with computational tools has provided information regarding the biosynthetic pathways of secondary metabolites. This information is leading to the modulation of associated metabolic pathways to expand the biotechnological and industrial applications of metabolites. The increased utilization of bioactive compounds requires sustainable production to improve the bioeconomy. In this review, the authors discuss the bioactive compounds isolated from Streptomyces and advanced approaches to improve their production. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd